Obesity, Akkermansia muciniphila, and Proton Pump Inhibitors: Is there a Link?. Issue 6 (November 2020) - Davis, Jessica A.; Collier, Fiona; Mohebbi, Mohammadreza; Stuart, Amanda L.; Loughman, Amy; Pasco, Julie A.; Jacka, Felice N.
Abstract: Objective: The gut bacterium Akkermansia muciniphila ( A. muciniphila ), has been linked to body composition and metabolism. However, the role of lifestyle factors and medication use in these relationships has not been considered. This study aimed to assess the relative abundance of A. muciniphila in participants and investigate its association with obesity, with consideration of potential confounding factors. Methods: Participants included 158 men of the Geelong Osteoporosis Study with dual-energy X-ray absorptiometry data, 16S rRNA gene bacterial profiling of stool samples, and lifestyle data. The relative abundance of A. muciniphila was estimated from total sequence reads, while obesity status was quantified by fat mass index (FMI, kg/m 2 ). Results: In this cohort (66 ± 12 yr, mean ± SD), the most common medications were proton pump inhibitors (PPIs) (28%), and these were associated with both high FMI and decreased abundance of A. muciniphila . Before and after adjustments for PPIs, participants with substantial A. muciniphila (abundance ≥0.1%, n = 94) compared to very low (abundance <0.1%, n = 64), had lower FMI (adjusted −1.33 (95%CI −2.30, −0.36) kg/m 2, p = 0.007). Conclusions: In this sample, relative abundance of A. muciniphila was inversely associated with high FMI, independent of PPI use. The relationship between obesity, reflux medication, and the gut microbiome warrants further investigation.